Injuries sustained in National Collegiate Athletic Association men's and women's basketball, 2009/2010-2014/2015 - Zuckerman, S. L.; Wegner, A. M.; Roos, K. G.; Djoko, A.; Dompier, T. P.; Kerr, Z. Y. (British Journal of Sports Medicine, 2018)
Background/aim: Recent rule changes regarding the safety of basketball athletes necessitate up-to-date reports of injury incidence. This study describes the epidemiology of injuries in men's and women's National Collegiate Athletic Association (NCAA) basketball during the 2009/2010-2014/2015 seasons.